Dark exciton signatures in time-resolved photoluminescence of single quantum dots - Smith, J; Dalgarno, P; Warburton, R; Gerardot, B; Petroff, P (2004)
Time-resolved photoluminescence of single charge tuneable quantum dots allows us to probe the differences in recombination dynamics between neutral and negatively charged excitons. We find that the luminescence decay from a neutral exciton contains a second lifetime component of several nanoseconds that is not present in the luminescence from singly or doubly charged excitons. We attribute the slowly decaying component to excitation cycles in which the initial exciton formed in the dot is dark, with angular momentum M = 2, and which subsequently scatters into the bright state with M = 1. The nature of the scattering mechanism is revealed by the dependence of the lifetime on the electrical bias applied across the charge-tuneable device. That the lifetime changes by an order of magnitude within a short bias range implies that the dark-to-bright transmutation does not occur through a simple spin flip. Rather it appears to come about by the dot briefly entering a higher energy charging state which allows exchange of the existing electron with another from the n-type contact region. We model the lifetimes and relative intensities of the two decay components using a simple rate equation analysis.